(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In the modern world, there is an ambiguous position regarding the influence of sugar on the human body. On the one hand, it has been proven that excess sugar in the diet is harmful to health and leads to a number of diseases. On the other hand, sugar, which produces carbohydrates, is a key link in the existence of most living organisms.